(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the development of cognitive process based on scientific approaches to improve the efficiency of work for children with mental retardation in performing numbering, counting and arithmetic operations from one to ten, using game activities in training, demonstration.Tayanch so’z va iboralar.